Bekymringsarbeidet Politiets forebygging av radikalisering og voldelig ekstremisme - Førde, Kristin Engh (Cappelen Damm Akademisk/NOASP (Nordic Open Access Scholarly Publishing), 2023)
Local police departments receive a vast number of calls annually from the healthcare sector, the education sector, the Norwegian Labour and Welfare Administration, other social service agencies, families, friends, neighbors and others, expressing concern that individuals or groups might be, or are at risk of becoming, violent extremists. The majority are unwarranted. Yet Norway has, in recent years, experienced that extremists can inflict a great deal of damage, pain, fear and death - not just on individual victims, but on society as a whole. How can the relevant authorities intervene in time to prevent such events from occurring without compromising important democratic values? This book takes a look at how local police perceive and carry out their role in the tremendously complex and demanding field we call 'concern work' (bekymringsarbeidet). The police face complicated dilemmas on a daily basis: What is the relationship between extreme behavior and expression, and extremist violence? Where are the boundaries between conservative and extreme forms of religion? Is there an appropriate moment for the police to confront persons who have not (yet?) broken any laws? Concern Work. Police Prevention of Radicalization and Violent Extremism will appeal to researchers and practitioners working with prevention initiatives, and anyone interested in radicalizaion and violent extremism, as well as democracy, freedom of speech and the rule of law.